Social housing and flexibility: bogota´s studi case. ¿why the inhabitants transform their habitat? (2006)
Nowadays in Bogotá, the production of housing state doesn’t satisfy the necessities of their users. Because, this kind of dwelling has the following troubles: little space for the daily activities, storage problems and space adjustments. Also, the intact dwelling is the exception and it doesn’t the rule. Under these conditions, any dwelling is modified. Consequently, these transformations happen because the inhabitants are looking for flexibility and they adapt the initial dwelling to their reality. Additionally, these modifications break the quality of the habitat. In this context, it is important to study the housing state flexibility. Because the researches has been centered only in the transformations of the informal housing. But a few researches has been studied the transformations of the formal housing. Likewise, they are reduced the studies that analyze the processes that lead to the flexibility in the housing. The essay explain the residential cluster concept. It exposes how the flexibility behaves in the residential clusters. Also, it proposes that the flexibility is an important agent to housing state design and habitat. Finally, it proposes a habitat explicative model.